2019
DOI: 10.1111/ggi.13820
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the association between optimal energy intake and all‐cause mortality in older patients with diabetes mellitus using the Japanese Elderly Diabetes Intervention Trial

Abstract: AimSelecting optimal energy intake during diet therapy for older patients with diabetes mellitus is difficult because of the large differences in physical function and comorbid diseases. In Japan, although requirements for total energy intake are calculated by multiplying a person's standard bodyweight (BW) by the amount of physical activity, evidence supporting the application of this method among older people is limited. Therefore, we aimed to assess optimal energy intake by evaluating the relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…The 2019 diabetes care guidelines of the Japan Diabetes Society recommend that the total energy intake requirement in older adults should be calculated using age-dependent target body weight (kg) = (22-25 kg/m 2 × height [m] 2 ) multiplied by coefficients of physical activity [117]. Using a target body weight set based on age-dependent coefficients (23.5 and 25.0 kg/m 2 for ages < 75 and ≥ 75 years, respectively), we found a U-shaped association between energy intake per target body weight and mortality similar to that reported for the association between energy intake per real body weight and mortality [116].…”
Section: Energy Intakesupporting
confidence: 76%
See 1 more Smart Citation
“…The 2019 diabetes care guidelines of the Japan Diabetes Society recommend that the total energy intake requirement in older adults should be calculated using age-dependent target body weight (kg) = (22-25 kg/m 2 × height [m] 2 ) multiplied by coefficients of physical activity [117]. Using a target body weight set based on age-dependent coefficients (23.5 and 25.0 kg/m 2 for ages < 75 and ≥ 75 years, respectively), we found a U-shaped association between energy intake per target body weight and mortality similar to that reported for the association between energy intake per real body weight and mortality [116].…”
Section: Energy Intakesupporting
confidence: 76%
“…The mortality risk was higher in Q1 (<24.85 kcal/kg body weight/day) and Q4 (≥34.79 kcal/kg body weight/day) than in Q2 (24.86-29.73 kcal/kg body weight/day) and Q3 (29.74-34.78 kcal/kg body weight/day) The risk of Q1 against Q3 was significant, whereas the risk of Q4 against Q3 was not. The lowest mortality risk was observed in Q2 comprising younger old patients (<75 years), whereas the lowest risk in older old patients (≥75 years) was observed in Q3 [116]. These results indicate that low energy intake is a mortality risk for older patients with diabetes and that energy requirement per actual body weight should be set higher in older old patients than in younger ones.…”
Section: Energy Intakementioning
confidence: 69%
“…In particular, dietary intake has the greatest effect on the status of frailty [ 14 15 ]. Previous studies reported that the intake of total energy, protein, vitamin D, and calcium determined frailty, hospitalization rate, and mortality [ 16 17 18 19 20 ]. The elderly population consuming enough protein and vitamin D showed improved physical function and increased muscle mass [ 21 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between energy intake and the mortality is highly complex due to the cross-study heterogeneity including differences in study subjects (healthy vs. ill), study periods, and proportions of specific macronutrients (carbohydrates, protein, and fat), which cannot be easily adjusted for meta-analyses. In general, greater energy intake is associated with increased risk of mortality including risk of cardiovascular and cancer death in the general population and in patients with chronic diseases such as type 2 diabetes mellitus and end-stage CKD [17,19,30], whereas it is associated with lower mortality in critically ill patients with low BMI [31]. On the other hand, lower energy intake increases the risk of mortality in patients with chronic diseases [17,19] and in elderly people [32], and a favorable effect of lower energy intake on longevity that has been observed in animal studies remains controversial in human studies [33,34].…”
Section: Discussionmentioning
confidence: 99%